Etika Bermedia Sosial dan Menyikapi Berita Bohong (HOAX): Studi Takhrij dan Syarah Hadits - Dewi Nurelisa; Muhamad Yoga Firdaus; Irwan Abdurrohman (UIN Sunan Gunung Djati Bandung, 2022)
Humans are known as social creatures who cannot be separated from the activities that are interconnected with other humans. With this relationship activity, humans work by themselves to communicate with each other. In the sequel, relationships are not only carried out spontaneously in concrete activities but can also be carried out through virtual media and using social media accounts. However, in the implementation of relations on social media, violations of the relationship policy are being found, including the dissemination of fake news and hatred. As a result, there must be an increase in the ethics of relations or communication in Islam. Communication ethics in Islam is not only approved as scientific knowledge but there are suggestions in communication activities in social media. With this knowledge and application, you can pass on good knowledge of the essentials of communication ethics in social media, because social media is not only a medium of communication but a percentage of relationship habits in the modern world.